Effects of new and emerging therapies on gastrointestinal outcomes in cystic fibrosis. Issue 6 (November 2017) - Houwen, Roderick H.J.; van der Woerd, Wendy L.; Slae, Mordechai; Wilschanski, Michael
Abstract : Purpose of review: Several new therapeutic modalities have recently become available to be used in patients with cystic fibrosis such as potentiators, modulators, and probiotics. Although the effects on pulmonary function have been well documented, gastrointestinal outcomes have been addressed only rarely. Recent findings: Both the potentiator (ivacaftor) and the potentiator/modulator combination (ivacaftor/lumacaftor) that are currently on the market have a positive effect on BMI. Young patients (2–5 years of age) with a gating mutation may show improvement of exocrine pancreatic function on ivacaftor. In this specific patient population this agent also seems to improve intestinal pH and reflux. The effect of these medications on other gastrointestinal outcomes, such as intestinal inflammation and cystic fibrosis liver disease, has not been described so far. Furthermore, the results of several trials suggest that probiotics might reduce intestinal inflammation. Finally, organoids might be used to predict in vitro the clinical effect of potentiators and modulators. Summary: The effect of new interventions on the gastrointestinal outcomes studied so far is favourable. Future studies should address the effect on other gastrointestinal parameters.